Lao People's Democratic Republic : Assessment Letter for the Asian Development Bank and the World Bank. (Policy Papers; Policy Paper, 2005)
This note provides an update of the assessment of Lao P.D.R.'s macroeconomic conditions and outlook presented at the time of the 2004 Article IV.